Computational Screening of Efficient Single‐Atom Catalysts Based on Graphitic Carbon Nitride (g‐C3N4) for Nitrogen Electroreduction. Issue 6 (13th December 2018) - Chen, Zhe; Zhao, Jingxiang; Cabrera, Carlos R.; Chen, Zhongfang
Abstract: The development of low‐cost and efficient electrocatalysts for nitrogen reduction reaction (NRR) at ambient conditions is crucial for NH3 synthesis and provides an alternative to the traditional Harber‐Bosch process. Herein, by means of density functional theory (DFT) computations, the catalytic performance of a series of single metal atoms supported on graphitic carbon nitride (g‐C3 N4 ) for NRR is evaluated. Among all the candidates, the Gibbs free energy change of the potential‐determining step for five single‐atom catalysts (SACs), namely Ti, Co, Mo, W, and Pt atoms supported on g‐C3 N4 monolayer, is lower than that on the Ru(0001) stepped surface. In particular, the single tungsten (W) atom anchored on g‐C3 N4 (W@g‐C3 N4 ) exhibits the highest catalytic activity toward NRR with a limiting potential of −0.35 V via associative enzymatic pathway, and can well suppress the competing hydrogen evolution reaction. The high NRR activity and selectivity of W@g‐C3 N4 are attributed to its inherent properties, such as significant positive charge and large spin moment on the W atom, excellent electrical conductivity, and moderate adsorption strength with NRR intermediates. This work opens up a new avenue of N2 reduction for renewable energy supplies and helps guide future development of single‐atom catalysts for NRR and other related electrochemical process. Abstract : Searching for highly efficient and stable electrocatalysts for N2 fixation is critical to NH3 synthesis. Here, it is proposed that a single tungsten atom anchored on g‐C3 N4 exhibits superior catalytic performance for N2 reduction to NH3 due to its low limiting potential, significant suppressing effect for HER, and good stability.